EFEKTIFITAS PENGELOLAAN DANA DESA UNTUK PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT DESA DI KABUPATEN BONDOWOSO - Boedijono, Boedijono; Wicaksono, Galih; Puspita, Yeni; Bidhari, Sandhika Cipta; Kusumaningrum, Nurcahyaning Dwi; Asmandani, Venantya (Economic Faculty, Attahiriyah Islamic University, 2019)
The purpose of this study was to find out how to manage village finance and the effectiveness of managing village funds for development and economic empowerment of rural communities in Bondowoso District. Three sub-districts in the Bondowoso District, namely Curahdami, Wonoasri, and Tenggarang Subdistricts as field area, and the combination of quantitative and qualitative methods were used. The results of this study indicate that: the villages in Bondowoso District have managed village finances well, but in certain cases, they are still not orderly in administration, so that they sometimes experience delays in disbursing village finance for the following period. The discussion and implications of the findings are discussed in the article.